A High Performance Electrochemical Sensor for Pb2+ Ions Based on Carbon Nanotubes Functionalized CoMn2O4 Nanocomposite. Issue 26 (9th July 2020) - Bashir, Nagina; Akhtar, Mehwish; Nawaz, Hafiza Zahra Rab; Warsi, Muhammad Farooq; Shakir, Imran; Agboola, Philips O; Zulfiqar, Sonia
Abstract: An efficient electrochemical sensor for the trace level detection of heavy metal ion (Pb 2+ ) was successfully developed using carbon nanotubes functionalized CoMn2 O4 nanocomposite. The structural and morphological studies of prepared nanocomposite were confirmed by means of XRD, FTIR, FESEM and EDX analyses. Electrochemical properties were investigated by means of EIS and CV studies using standard potassium ferrocyanide as a redox couple while the stripping behaviour of fabricated electrode was determined by square wave anodic stripping voltammetry (SWASV). Effect of various parameters such as deposition potential, stripping medium and deposition time were analyzed to have best detecting response on modified electrode. The designed sensor exhibited excellent sensitivity, selectivity, stability along with good reproducibility for the detection of lead ions which can be ascribed to the integrated high adsorption capacity of CoMn2 O4 and large surface area of carbon nanotubes. A linear relationship between current response and lead ion concentrations was obtained in the range from 0.01 μM to 0.85 μM with a detection limit of 0.004 μM. Moreover, the developed sensor was not much affected by the presence of other foreign species. From these results, it is expected that the developed sensor can be applied for detection of various organic, metallic and organometallic environmental toxins with slight modification. Abstract : An efficient transducer for the electrochemical detection of lead ions was developed using CoMn2 O4 /CNT nanocomposite as a recognition layer. The developed sensor demonstrated absolute discrimination ability, remarkable electrocatalytic activity, good reproducibility, high stability and extraordinary sensitivity for lead ions detection in real water samples even in the presence of various foreign species.